Pengaruh Sistem Informasi Akuntansi dan Kinerja Sumber Daya Manusia Terhadap Peningkatan Pendapatan BUM Desa di Kabupaten Gianyar: Abstrak - Wiranata, Agung Adi; Kawisana, Putu Gede Wisnu Permana; Yoga, I Gusti Agung Prama (Universitas Warmadewa, 2023)
The purpose of this study is to empirically examine the effect of accounting information systems and human resource performance on increasing the income of Village-Owned Enterprises (BUM Desa) in Gianyar Regency. This research was conducted in all Village-Owned Enterprises (BUM Desa) in Gianyar Regency using quantitative research methods Data collection from this study was carried out by distributing questionnaires. The sample of this study was 64 respondents. The analysis technique used is multiple linear regression analysis with the help of SPSS program version 29. The results of this study show that the accounting information system has a positive and significant effect on increasing the income of Village-Owned Enterprises (BUM Desa) in Gianyar Regency, and the performance of human resources has a positive and significant effect on increasing the income of Village-Owned Enterprises (BUM Desa) in Gianyar Regency.